1998
DOI: 10.1111/j.1471-0528.1998.tb10172.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparative trial of the intrauterine system and norethisterone levonor gestrel for treatment of idiopathic menorrhagia

Abstract: Objective To compare the efficacy and acceptability of the levonorgestrel intrauterine system and Design A randomised comparative parallel group study. Setting Gynaecology outpatient clinic in a teaching hospital. Participants Forty-four women with heavy regular periods and a measured menstrual blood loss exceeding 80 ml. Methods Twenty-two women had a levonorgestrel intrauterine system inserted within the first seven days of menses, and 22 women received norethisterone (5 mg three times daily) from day 5 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
180
0
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(188 citation statements)
references
References 19 publications
1
180
0
7
Order By: Relevance
“…[12][13][14][15] This study demonstrates that norethisterone or COC pills-mediated improvements in menorrhagia extend to adolescents. Progesterone can be used cyclically in two different treatment Protocols-as short course during luteal phase and a relatively longer course lasting 21 days from day 5 of cycle.…”
Section: Discussionmentioning
confidence: 59%
“…[12][13][14][15] This study demonstrates that norethisterone or COC pills-mediated improvements in menorrhagia extend to adolescents. Progesterone can be used cyclically in two different treatment Protocols-as short course during luteal phase and a relatively longer course lasting 21 days from day 5 of cycle.…”
Section: Discussionmentioning
confidence: 59%
“…The LNG-IUS was found to be more effective than tranexamic acid. 9 In a comparative study, Irvine et al (1998), reported that LNG-IUS was effective in reducing menstrual blood loss by 94% compared to 87% by oral norethisterone. The patient satisfaction rate with LNG-IUS was higher compared to oral norethisterone.…”
Section: Efficacy Of Levonorgestrel Intrauterine Systemmentioning
confidence: 99%
“…The patient satisfaction rate with LNG-IUS was higher compared to oral norethisterone. 12 In a pilot, non-comparative study, Montereio I et al (2002) evaluated the efficacy and performance of an intrauterine system releasing levonorgestrel (LNG-IUS, Mirena) 20 microgm/day for up to one year in the treatment of 44 adult women with menorrhagia. 13 These patients were inserted LNG-IUS after the failure of other medical therapies.…”
Section: Efficacy Of Levonorgestrel Intrauterine Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report reduction of blood loss in menstrual cycles up to 97%, with its maximum efficacy 1 year after insertion [24,[28][29][30][31]. The majority of women with Mirena® bleed only for 1 day or experience just spotting during their period, while 15% of them become amenorrheic [31].…”
Section: Levonorgestrel-releasing Intrauterine Devicementioning
confidence: 99%